The Unhealthy = Tasty Intuition and Its Effects on Taste Inferences, Enjoyment, and Choice of Food Products - Raghunathan, Rajagopal; Naylor, Rebecca Walker; Hoyer, Wayne D. (Journal of Marketing, 2006)
Across four experiments, the authors find that when information pertaining to the assessment of the healthiness of food items is provided, the less healthy the item is portrayed to be, (1) the better is its inferred taste, (2) the more it is enjoyed during actual consumption, and (3) the greater is the preference for it in choice tasks when a hedonic goal is more (versus less) salient. The authors obtain these effects both among consumers who report that they believe that healthiness and tastiness are negatively correlated and, to a lesser degree, among those who do not report such a belief. The authors also provide evidence that the association between the concepts of “unhealthy” and “tasty” operates at an implicit level. The authors discuss possibilities for controlling the effect of the unhealthy = tasty intuition (and its potential for causing negative health consequences), including controlling the volume of unhealthy but tasty food eaten, changing unhealthy foods to make them less unhealthy but still tasty, and providing consumers with better information about what constitutes “healthy.”